Assessing the Efficacy of Alternatives to Incarceration within Seven Federal Districts. (2nd January 2020) - Wolff, Kevin T.; Baber, Laura M.; Dozier, Christine A.; Cordeiro, Roberto
Abstract: Though alternatives to incarceration (ATI) courts have existed in the state system for 30 years, such courts are a relatively new phenomena at the federal level. We assess the impact of participation in an ATI program on a number of outcomes using a quasi-experimental matching design. Results suggest that defendants who successfully completed an ATI program were employed a greater percentage of the days, and received favorable case dispositions and less severe sentences.